2022
DOI: 10.1186/s10194-021-01371-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring alterations in sensory pathways in migraine

Abstract: Background Migraine is a neurological disorder characterized by intense, debilitating headaches, often coupled with nausea, vomiting and sensitivity to light and sound. Whilst changes in sensory processes during a migraine attack have been well-described, there is growing evidence that even between migraine attacks, sensory abilities are disrupted in migraine. Brain imaging studies have investigated altered coupling between areas of the descending pain modulatory pathway but coupling between so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Rather than a dysfunction in a single area of the brain, migraine can be regarded as a dysfunction of sensory processing which ultimately generates episodes of pain [ 23 ]. Functional neuroimaging showed that migraine is related to a heightened connectivity among the different sensory areas of the brain [ 24 ]. Thus, migraine is regarded as a “connectopathy” rather than a disease arising from dysfunctioning of specific areas of the brain.…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…Rather than a dysfunction in a single area of the brain, migraine can be regarded as a dysfunction of sensory processing which ultimately generates episodes of pain [ 23 ]. Functional neuroimaging showed that migraine is related to a heightened connectivity among the different sensory areas of the brain [ 24 ]. Thus, migraine is regarded as a “connectopathy” rather than a disease arising from dysfunctioning of specific areas of the brain.…”
Section: Biological Mechanisms Underlying Migrainementioning
confidence: 99%
“…The CUN is a wedge-shaped cortical region located inside the occipital lobe, posterior to the parietal occipital fissure and superior to the CAL. The CUN consists of both striatal and extrastriatal visual cortex; it receives direct input from the lateral geniculate body (Leopold, 2012 ; Meylakh and Henderson, 2022 ). Chen et al ( 2021a ) reported that patients with active TAO exhibited significantly decreased spontaneous brain activity in the MOG; this decreased activity was associated with visual deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed potential changes in the neurophysiology during the interictal phase. One study using fMRI in 32 patients with migraine during the interictal phase found altered global sensory processing in the pain-free state, providing a neurophysiological basis for a potentially altered auditory, gustatory, motor and somatosensory processing ( 87 ). A proton magnetic resonance spectroscopy (1H-MRS) and fMRI daily in one patient for 21 days identified interictal abnormalities that could suggest an increased susceptibility to excitatory migraine triggers ( 88 ).…”
Section: “Objective” Interictal Findingsmentioning
confidence: 99%